Physical and Thermal Characterization of Glass Ceramics Prepared from Cullet and Coal Bottom Ash - Mayzan, Mohd Zul Hilmi (2010)
This thesis describes the physical and thermal characterization of glass ceramics prepared from mixtures of soda lime cullet glass and coal bottom ash. The aim of this research is to develop and optimize the phase and structural properties, microstructure, density, linear shrinkage and Vickers micro hardness as well as to determine the thermal diffusivity behavior of glass ceramics. Three batch compositions of glass ceramics were obtained by mixing 50-90 weight percent of soda lime cullet glass with 10-50 weight percent of coal bottom ash, undergone the vitrification method by melting the compositions at 1450°C for 3 hours and heat treating the compacted powdered glasses between 700 and 1000°C for 2 hours at 100°C intervals. The vitrification method offered a solution for the disposal of soda lime cullet glass and coal bottom ash as well as to minimize their hazardous effects to the environment. The resulting samples were characterized by using several characterization techniques involving X-ray fluorescence spectroscopy, differential thermal analysis, X-ray diffraction, scanning electron microscope with energy dispersive X-ray, optical microscope, density, linear shrinkage, Vickers micro hardness and thermal diffusivity determination by using flash method. The differential thermal analysis on all powdered glasses revealed that the crystallization temperature occur above 700°C. The crystalline phases were identified as wollastonite [CaSiO3], augite, aluminian [Ca(Mg,Fe,Al)(Si,Al)2O6] and albite, disordered [NaAlSi3O8]. Wollastonite crystals had whisker-type with acicular grains and needle-like morphologies, augite, aluminian crystals had feather-like and small oval-like morphologies while samples that have crystalline phases of augite, aluminian and albite, disordered had scratch-like morphologies. The measured density, linear shrinkage, Vickers micro hardness and thermal diffusivity for all heat treated samples were in range of 2.70 to 2.76 g/cm3, 0.83 to 14.04 %, 496.2 to 747.9 kg/mm² and 0.133 to 0.766 mm2/s respectively. Generally, the glass content in heat treated samples is responsible in reducing the density, Vickers micro hardness and thermal diffusivity values. According to the findings in all characterization techniques, the most promising heat treated samples at each batch composition were suitable for industrial use, especially in the manufacturing of tiles.